Study on the Subjective Well-Being of Healthy Siblings of Adolescent Special Children in COVID-19 Period - Leyi Shao, WenLung Chang, Guangning Luo, Guozhi Chen, Linli Zhu, Xia Chen (Forest Chemicals Review, 1970)
In this paper, special children's healthy adolescent siblings are studied in a mixed way of quantitative and qualitative research, to explore their current situation of life satisfaction and emotion in adolescence, and to understand their emotional situation towards family, college, study and community. Results: Special children's healthy adolescent siblings have high satisfaction with college and family, while their freedom satisfaction and academic satisfaction are lower than other factors. Female special children's healthy adolescent siblings have lower life satisfaction and higher negative emotion. Special children's healthy adolescent siblings in rural areas have lower life satisfaction and negative emotion. Special children's healthy adolescent siblings who live with their parents have higher life satisfaction and positive emotion. The subjective well-being of special children's healthy children siblings is related to the interaction time with special children. Special children's healthy adolescent siblings who interact with their parents for more than two hours a week have high family satisfaction, friendship satisfaction and positive emotion. This study is of great significance in supporting the psychological development of special children's health.